Development and Implantation of a Universal Talar Prosthesis - Bowes, Julia; Adeeb, Samer; Grosvenor, Andrew; Beaupre, L.; Jomha, Nadr M. (Frontiers in Surgery, 2019)
Talar avascular necrosis (AVN) can result in bone collapse with subsequent ankle and subtalar osteoarthritis ending in significant pain and disability. Custom talar body prostheses have been implanted with good results but these are difficult to design, costly and require extensive planning. In the past few years, we have investigated the feasibility of a universal talar replacement prosthesis through multiple studies. This report documents that development and the results from the first patient to receive a universal talar replacement prosthesis. A patient with bilateral talar AVN with collapse had implantation of two universal talar prostheses with final evaluations at 34 months (right) and 12 months (left) post implantation using visual analogue scale, range of motion, SF-36 questionnaire, and personal reflection. The patient had decreased pain, increase range of motion, improvement (or no change) on all domains of the SF-36 and expressed great appreciation for having the procedures done. This report demonstrates the effectiveness and feasibility of a universal talar prosthesis. Continued development of this type of implant can decrease costs, improve access and provide an acceptable alternative when a custom prosthesis is not possible.